Nuclear accumulation of CDH1 mRNA in hepatocellular carcinoma cells - Ghafoory, Shahrouz; Mehrabi, Arianeb; Hafezi, Mohammadreza; Cheng, Xinlai; Breitkopf-Heinlein, Katja; Hick, Meike; Huichalaf Carbonell, Mariela; Herbel, Vera; Saffari, Arash; Wölfl, Stefan (Oncogenesis, 2015)
Expression of E-cadherin has a central role in maintaining epithelial morphology. In solid tumors, reduction of E-cadherin results in disruption of intercellular contacts. Consequently, cells lose adhesive properties and gain more invasive mesenchymal properties. Nevertheless, the mechanism of E-cadherin regulation is not completely elucidated. Here we analyzed the distribution of E-cadherin expression at the cell level in human hepatocellular carcinoma, in which human liver paraffin blocks from 25 hepatocellular carcinoma patients were prepared from cancerous (CA) and noncancerous areas (NCA). In situ hybridization (ISH) was performed to detect E-cadherin and hypoxia-induced factor-1α (HIF1α) mRNAs and immunohistochemistry to stain E-cadherin protein. In parallel, RNA was extracted from CA and NCA, and E-cadherin and HIF1α were quantified by quantitative reverse transcription PCR. ISH revealed abundant E-cadherin mRNA in nuclei of hepatocellular carcinoma cells (HCCs), whereas immunohistochemistry showed depletion of E-cadherin protein from these areas. In sections of NCA, E-cadherin mRNA was also found in the cytosol, and E-cadherin protein was detected on the membrane of cells. Experiments in cell lines confirmed E-cadherin mRNA in nuclei of cells negative for E-cadherin protein. HIF1α expression is elevated in CAs, which is associated with a clear cytosolic staining for this mRNA. Our results demonstrate that E-caderhin mRNA is selectively retained in nuclei of HCCs, whereas other mRNAs are still exported, suggesting that translocation of E-cadherin mRNA from nuclei to cytoplasm has a role in regulating E-cadherin protein levels during epithelial mesenchymal transition.